2013
DOI: 10.1002/chem.201300600
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Stabilized and Atomically Precise Gold Nanocluster Catalysis: A Case Study for Correlating Fundamental Electronic Properties with Catalysis

Abstract: We present results from our investigations into correlating the styrene-oxidation catalysis of atomically precise mixed-ligand biicosahedral-structure [Au25(PPh3)10(SC12H25)5Cl2](2+) (Au25-bi) and thiol-stabilized icosahedral core-shell-structure [Au25(SCH2CH2Ph)18](-) (Au25-i) clusters with their electronic and atomic structure by using a combination of synchrotron radiation-based X-ray absorption fine-structure spectroscopy (XAFS) and ultraviolet photoemission spectroscopy (UPS). Compared to bulk Au, XAFS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 68 publications
(133 reference statements)
6
100
1
Order By: Relevance
“…This result is also consistent with the DFT calculations of Schatz et al [ 31 ] that show that for this species with an odd number of electrons the ground state is a magnetic doublet. An interesting aspect of this system is that we have analyzed in detail the spin density for this cluster and found that it is larger in the surface than in the core ( Figure 3 ), which indicates that magnetism is a surface effect, a result that might have considerable importance in understanding its infl uence on catalysis [ 32 ] and that also differs from earlier observations attributing the magnetic behavior to the core. [ 31 ] The dominance of surface magnetization is strongly sizedependent as eventually, as the number of atoms increases, the behavior of the core will dominate the magnetic behavior of the nanoparticle.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…This result is also consistent with the DFT calculations of Schatz et al [ 31 ] that show that for this species with an odd number of electrons the ground state is a magnetic doublet. An interesting aspect of this system is that we have analyzed in detail the spin density for this cluster and found that it is larger in the surface than in the core ( Figure 3 ), which indicates that magnetism is a surface effect, a result that might have considerable importance in understanding its infl uence on catalysis [ 32 ] and that also differs from earlier observations attributing the magnetic behavior to the core. [ 31 ] The dominance of surface magnetization is strongly sizedependent as eventually, as the number of atoms increases, the behavior of the core will dominate the magnetic behavior of the nanoparticle.…”
mentioning
confidence: 85%
“…Detection of room temperature ferromagnetism in APGCs is anticipated to lead to hitherto undiscovered applications involving a combination of magnetism and quantum size effects. These fi ndings in combination with recent efforts to correlate fundamental electronic structure of atomically precise gold clusters with their catalytic properties [ 32 ] , [ 34 ] are just the fi rst steps in meeting one of the grand science challenges to understand how remarkable properties emerge from complex correlations of their atomic or electronic constituents. [ 35 ] …”
mentioning
confidence: 98%
“…The XANES spectrum of the starting material demonstrates the features of CuO, and these features are reduced with increasing tempera- Reprinted with permission from Ref. [57]. Copyright 2013, Wiley-Blackwell.…”
Section: Oxide Nanoparticlesmentioning
confidence: 99%
“…Thiol ligands possess electron-withdrawing properties and favour a shift of the centre of the electron density of Au d-levels in the cluster towards the Fermi level. 326 This can be a reason for the catalytic activity of Au n (SR) m . 322 Gold clusters are used for catalysis in solution or as supported composites (Fig.…”
Section: Viii2 Application Of Au N (Sr) M and Au N (Pr 3 ) M Clustementioning
confidence: 99%